SISTEM PERWAKILAN MENURUT UUD 1945 DAN SISTEM PERWAKILAN YANG IDEAL PADA PERUBAHAN UUD BERIKUTNYA - Anwar Cengkeng (Legal Spirit, 2017)
The formulation of the 1945 Constitution (original text) elects the MPR as a representative system consisting of members of the House of Representatives coupled with regional representatives and group representatives. In the third amendment of the 1945 Constitution, the representative system agreed upon by MPR members is a representative MPR system consisting of members of the DPR and DPD members. The system of representation in the amendment of the 1945 Constitution places the DPR and DPD in the same position, but different in its authority, the DPR has full authority as a legislative body, while the DPD which is the regional representative is only complementary. For the amendment of the 1945 Constitution, it is necessary to rearrange the MPR, but to function only as a meeting place between DPR and DPD, the authority of DPD should not be equal to the authority of DPR, but the limited authority must be fully owned, as in the case of full authority to determine Certain laws with the President and the House of Representatives. Keywords: Representative system, MPR, DPR, and DPD